Lithium secondary battery positive electrode active material and lithium secondary battery comprising the same
Patent Information
- Application Number
- CN202580023709.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-27
AI Technical Summary
然而,在这种情况下,颗粒表面部会生成岩盐(Rock salt)结构,存在正极活性材料的电化学性能下降的问题
根据本实施例,锂二次电池正极活性材料通过适当控制制备工艺,使其满足由单颗粒的第一至第三直径构成的关系式的特定范围,从而可以提高稳定性和电化学特性。
Smart Images

Figure CN122996512A_ABST
Abstract
Description
Technical Field
[0001] This embodiment relates to a positive electrode active material for a lithium secondary battery, a method for preparing the same, and a lithium secondary battery containing the same. Background Technology
[0002] Recently, demand for IT mobile devices, small electric drive devices (e-bikes, small EVs, etc.), and energy storage devices (Energy Storage Systems (ESS)) has been exploding. Therefore, the development of high-capacity and high-energy-density rechargeable batteries to power these devices is actively underway globally. To manufacture such high-capacity batteries, high-capacity cathode materials must be used.
[0003] Among existing layered cathode active materials, LiNiO2 has the highest capacity, but it is prone to structural collapse during charge and discharge, and its oxidation number problem leads to low thermal stability, making it difficult to commercialize.
[0004] To address the aforementioned issues, it is necessary to replace the unstable Ni sites with other stable transition metals (such as Co and Mn). Therefore, ternary NCM systems substituted with Co and Mn have been developed.
[0005] Traditional NCM (Non-Metallic Chemical Coating) cathode active materials are composed of secondary particles formed by the aggregation of primary particles. However, for cathode materials composed of secondary particles formed by the aggregation of primary particles ranging from tens of nanometers to several micrometers in size, the large specific surface area of the powder and the wide contact area with the electrolyte result in a high probability of gas generation. Furthermore, the secondary particles are relatively weak, and during the electrode pressing process, there is a problem of secondary particles breaking into primary particle shapes, leading to a deterioration in lifespan characteristics.
[0006] To address this issue, some have proposed avoiding the secondary particle morphology of primary particle aggregation and instead maximizing the size of the primary particles to prepare the cathode material for application. However, in this case, rock salt structures form on the particle surface, leading to a decrease in the electrochemical performance of the cathode active material.
[0007] Therefore, there is an urgent need to develop a positive electrode active material that, by determining the appropriate size of the primary particles, can not only improve the lifespan stability of the battery, but also exhibit excellent electrochemical properties such as charge and discharge capacity. Summary of the Invention
[0008] Technical problems to be solved This embodiment aims to provide a positive electrode active material for lithium secondary batteries, a method for preparing the same, and a lithium secondary battery containing the same. The positive electrode active material is a single-crystal positive electrode active material. The first to third diameters of the single particles are derived by SEM (scanning electron microscope) image analysis. The single particles satisfy a specific range of the relationship formed by the first to third diameters, thereby improving electrochemical characteristics and stability.
[0009] Technical solution This application claims priority to Korean Patent Application No. 10-2024-0043323, filed on March 29, 2024, the entire contents of which are incorporated herein by reference.
[0010] According to one embodiment of a lithium secondary battery positive electrode active material, wherein the lithium secondary battery positive electrode active material is a monocrystalline lithium secondary battery positive electrode active material, the positive electrode active material comprises a morphology of 1 to 20 single particles aggregated together, the single particles satisfying the following formula 1.
[0011] [Formula 1] 1.40μm≤(D1 D2) / D3≤1.70μm In Equation 1, D1 refers to the first diameter of a single particle derived from the perimeter of a single particle measured in the SEM (scanning electron microscope) image of the positive electrode active material, assuming it to be the perimeter of an ideal circle (2πR1). (D1=2πR1) R1), D2 refers to the area of a single particle measured in the SEM image of the positive electrode active material, assumed to be the area of an ideal circle (πR2). 2 The second diameter of a single particle (D2=2) was derived afterward. R2), D3 refers to the third diameter of a single particle derived from the circumcircle diameter of the particle measured in the SEM image of the positive electrode active material (D3=2). R3).
[0012] According to another embodiment, a method for preparing a positive electrode active material for a lithium secondary battery includes the following steps: preparing a transition metal precursor containing 50 to 70 mol% nickel based on the total molar amount of the transition metal; mixing the transition metal precursor and lithium raw materials and then calcining to form a lithium transition metal oxide; and crushing the lithium transition metal oxide to form a monocrystalline positive electrode active material for a lithium secondary battery, wherein the crushing can be carried out at a crushing pressure of 3.4 to 4.5 bar, and the calcination can be carried out in an air atmosphere.
[0013] According to yet another embodiment, the lithium secondary battery can be a lithium secondary battery comprising a lithium secondary battery positive electrode, the lithium secondary battery positive electrode comprising the positive electrode active material according to one embodiment.
[0014] Beneficial effects According to this embodiment, the positive electrode active material of lithium secondary battery can be improved in terms of stability and electrochemical characteristics by appropriately controlling the preparation process to make it meet a specific range of the relationship between the first to third diameters of a single particle.
[0015] Accordingly, the lithium secondary battery prepared in this embodiment can improve electrochemical performance such as stability and capacity. Attached Figure Description
[0016] Figure 1 This is an SEM image of the positive electrode active material prepared in Example 1.
[0017] Figure 2 This is an SEM image of the positive electrode active material prepared in Example 2.
[0018] Figure 3 This is an SEM image of the positive electrode active material prepared in Example 3.
[0019] Figure 4 This is an SEM image of the positive electrode active material prepared in Example 4.
[0020] Figure 5 This is a SEM image of the positive electrode active material prepared in Comparative Example 3.
[0021] Figure 6 This is a SEM image of the positive electrode active material prepared in Comparative Example 4.
[0022] Figure 7 The image is an image from an SEM image of the positive electrode active material prepared in Example 1, which was analyzed using an AI-based program.
[0023] Figure 8 The image is an image from an SEM image of the positive electrode active material prepared in Example 2, which was analyzed using an AI-based program.
[0024] Figure 9 The image is an image analysis performed using an AI-based program on the SEM image of the positive electrode active material prepared in Example 3.
[0025] Figure 10 The image is an image analysis performed using an AI-based program on the SEM image of the positive electrode active material prepared in Example 4.
[0026] Figure 11 The image is an image from an SEM image of the positive electrode active material prepared in Comparative Example 3, which was analyzed using an AI-based program.
[0027] Figure 12 The image is an image analysis based on an AI program performed on the SEM image of the positive electrode active material prepared in Comparative Example 4. Detailed Implementation
[0028] The terms "first," "second," "third," etc., are used to describe various parts, components, regions, layers, and / or segments, but these parts, components, regions, layers, and / or segments should not be limited by these terms. These terms are only used to distinguish one part, component, region, layer, and / or segment from another. Therefore, without departing from the scope of the invention, the first part, component, region, layer, and / or segment described below can also be described as a second part, component, region, layer, and / or segment.
[0029] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention. Unless the context clearly indicates otherwise, the singular forms used are intended to include the plural forms as well. It should also be understood that the term "comprising" as used in the specification can specifically refer to a particular feature, domain, integer, step, action, element, and / or component, and does not exclude the presence or addition of other features, domains, integers, steps, actions, elements, and / or components.
[0030] When referring to a part as being "above" or "on top of" another part, it can mean that the part is directly above or on top of the other part, or that there are other parts in between. Conversely, when referring to a part as being "directly above" another part, there are no other parts in between.
[0031] Although not otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Terms defined in dictionaries should be interpreted as having the same meaning as disclosed in relevant technical literature and herein, and should not be interpreted in an idealized or overly formal sense.
[0032] In addition, unless otherwise specified, % refers to mol%.
[0033] In this specification, the term "combination" as used in the Markush form refers to a mixture or combination of one or more of the constituent elements described in the Markush form, which means including one or more of the constituent elements described above.
[0034] The embodiments of the present invention will be described in detail below to enable those skilled in the art to implement the invention. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.
[0035] Lithium secondary battery positive electrode active materials As mentioned earlier, existing positive electrode active materials for lithium secondary batteries have the following problems: due to the reduction in energy density and capacity and the breakage of particles during compression, the increased surface area leads to increased electrolyte exposure, which in turn leads to increased gas production inside the battery and a decrease in electrochemical characteristics.
[0036] However, in this embodiment, the first to third diameters of a single particle are derived by analyzing SEM (scanning electron microscope) images of the single-crystal positive electrode active material, and the primary particles of the single-crystal positive electrode active material satisfy a specific range of the relationship between the first to third diameters, thereby solving the above-mentioned problem.
[0037] Specifically, according to one embodiment, the positive electrode active material of a lithium secondary battery is a monocrystalline lithium secondary battery positive electrode active material, which may contain a morphology of 1 to 20 single particles aggregated together.
[0038] In this specification, a single particle can refer to a single particle consisting of one particle. A single crystal positive electrode active material can be a single particle consisting of one particle, or it can be a form formed by the aggregation of 1 to 20 or 2 to 20 single particles. More preferably, it can simultaneously include the single particle and the form formed by the aggregation of the single particles.
[0039] At this time, it can be the positive electrode active material of a lithium secondary battery that satisfies the following formula 1 for the single particle.
[0040] [Formula 1] 1.40μm≤(D1 D2) / D3≤1.70μm In Equation 1, D1 refers to the first diameter of a single particle derived from the perimeter of a single particle measured in the SEM (scanning electron microscope) image of the positive electrode active material, assuming it to be the perimeter of an ideal circle (2πR1). (D1=2πR1) R1), D2 refers to the area of a single particle measured in the SEM image of the positive electrode active material, assumed to be the area of an ideal circle (πR2). 2 The second diameter of a single particle (D2=2) was derived afterward. R2), D3 refers to the third diameter of a single particle derived from the circumcircle diameter of the particle measured in the SEM image of the positive electrode active material (D3=2). R3).
[0041] For the first diameter (D1) to the third diameter (D3), it can be derived as follows: the SEM image is analyzed using an AI (artificial intelligence) program, and the perimeter, area and circumcircle of each single particle presented in the SEM image are measured.
[0042] In this context, the circumcircle refers to an ideal circle that includes the two or more outermost points of a single particle. This means that the interior of the circumcircle contains the entire area of the single particle.
[0043] The AI-based image analysis is as follows: After detecting particles in the SEM image, the area and perimeter of each particle can be calculated using a simple Python function. The unit here corresponds to pixels, so a scale bar can be used to convert to SI (International System of Units) units such as micrometers (μm).
[0044] When deriving the first diameter (D1) to the third diameter (D3), in addition to the derivation process, the accuracy in single particle size measurement can be further improved by taking SEM images multiple times (specifically 3 to 100 times or 10 to 30 times) and performing additional operations to confirm whether the SEM images correspond to the images confirmed by the image analysis based on the AI program.
[0045] By measuring the first diameter (D1) to the third diameter (D3), the degree of single-particle growth can be accurately measured, and potential risk factors during battery evaluation can be accurately identified, thereby enabling the utilization of positive electrode active materials exhibiting excellent electrochemical properties.
[0046] On the other hand, analyses performed using a particle size analyzer may not correspond to analyses performed using SEM images as described in this specification. In other words, analyses performed using a particle size analyzer may not accurately measure the degree of individual particle growth. Specifically, even in active material particles confirmed to be overlapping or aggregated from individual particles, the present invention can determine the size of each individual particle, but existing analytical methods may struggle to perform such analyses. Therefore, existing analytical methods may not be able to accurately identify potential risk factors when evaluating batteries.
[0047] Furthermore, in Equation 1, (D1) The D2 / D3 ratio can range from 1.45 to 1.70 μm or from 1.50 to 1.68 μm. By satisfying the range of Equation 1, both stability and high-capacity electrochemical properties can be achieved.
[0048] Specifically, at 67.8 kN / cm 2After pressurization, in the volume-based particle size distribution curve of the positive electrode active material, the proportion of microparticles with a size of less than 1.0 μm can be less than 5.0%. More specifically, this proportion of microparticles can be 0.5% to 4.5%, 1.0% to 4.0%, 2.0% to 4.0%, or 2.1% to 3.6%. This reduces the generation of microparticles due to breakage, ultimately avoiding gas generation problems caused by microparticles and maximizing battery safety.
[0049] Furthermore, in the case of a battery containing a positive electrode active material that satisfies the range of Formula 1, the discharge capacity can be 195.0 mAh / g or higher. More specifically, the discharge capacity can be 195.0 to 200.0 mAh / g or 195.8 to 198.0 mAh / g.
[0050] If the range exceeds that of Formula 1, the positive electrode active material will undergo excessive single-crystal growth, leading to significant structural shrinkage and inhibiting the diffusion and extraction of lithium ions within the positive electrode active material. This may result in a decrease in electrode capacity and rate performance.
[0051] Furthermore, if the pressure is below the range of Formula 1, a large amount of fine powder may be generated due to particle breakage when pressure is applied. Specifically, when applying 67.8 kN / cm... 2 Under pressure, the proportion of micro powder with a particle size of less than 1 μm can be above 5.0%.
[0052] While satisfying the range of Equation 1, the following ranges can be satisfied independently or simultaneously.
[0053] The D1 can be in the range of 1.90 to 2.39 μm, specifically in the range of 1.92 to 2.30 μm or 1.94 to 2.23 μm. D1 tends to decrease as the shape of a single particle approaches a circle. By satisfying the above-mentioned appropriate range, the positive electrode active material can exhibit the aforementioned stability and excellent electrochemical properties.
[0054] The D2 can be in the range of 1.40 to 2.10 μm, specifically in the range of 1.45 to 2.00 μm or 1.50 to 1.80 μm. The D2 can tend to increase as the shape of the single particle is closer to a circle. By satisfying the above-mentioned appropriate range, the positive electrode active material can exhibit the aforementioned stability and excellent electrochemical properties.
[0055] The D3 can be in the range of 1.90 to 2.50 μm, specifically in the range of 1.93 to 2.45 μm or 1.96 to 2.41 μm. The D3 can tend to decrease as the shape of a single particle approaches a circle. By satisfying the above-mentioned appropriate range, the positive electrode active material can exhibit the aforementioned stability and excellent electrochemical properties.
[0056] Furthermore, for the lithium-ion battery cathode active material, when measuring the volume-based particle size distribution of the cathode active material, the average particle size (D50) can be 2.0 to 5.5 μm, 2.5 to 5.0 μm, or 3.0 to 4.5 μm. As the average particle size of the cathode active material meets these ranges, the compaction density is increased, thereby improving the electrode energy density and exhibiting excellent stability characteristics. In this specification, the average particle size (D50) can be defined as the particle size corresponding to 50% of the volumetric accumulation in the particle size distribution curve. The average particle size (D50) can be measured, for example, using a conventional laser diffraction method.
[0057] Furthermore, the positive electrode active material for the lithium secondary battery may contain 50 to 70 mol% nickel (Ni) based on the total molar amount of transition metals. Excessive nickel content may lead to thermal safety issues (thermal propagation issues) and potentially increase costs. However, insufficient nickel content may result in excessively low capacity. Therefore, the positive electrode active material according to the present invention, with a nickel content of 50 to 70 mol%, exhibits excellent thermal safety, reduces manufacturing costs, and simultaneously achieves appropriate capacity.
[0058] More specifically, it can be represented by the following chemical formula 1.
[0059] [Chemical Formula 1] Li a [Ni x Co y Mn z M w O2 In the chemical formula 1, 0.8≤a≤1.2, 0.5≤x≤0.7, 0.05≤y≤0.2, 0≤z≤0.4, 0≤w<0.03, x+y+z+w=1, and M is Zr, Y, B, Al, Mg, Ti, Nb, W, Sc, Si, V, Fe, Y, Mo, Ce, Hf, Ta, La, Sr or a combination thereof.
[0060] In the positive electrode active material of the aforementioned chemical formula 1, lithium may contain a content corresponding to 'a' (i.e., 0.8 ≤ a ≤ 1.2). If 'a' is too small, the capacity may decrease; if 'a' is too large, the strength of the calcined positive electrode active material will increase, potentially making it difficult to pulverize, and the increased lithium byproducts may lead to increased gas production. Considering the effect of lithium content control on improving the capacity characteristics of the positive electrode active material and the sintering balance during the preparation of the active material, the lithium content is more preferably 0.9 ≤ a ≤ 1.1.
[0061] In the positive electrode active material of the aforementioned chemical formula 1, nickel may contain a content corresponding to x (i.e., 0.5 ≤ x ≤ 0.7). As mentioned earlier, if the nickel content is too low, it may be difficult to achieve high battery capacity; if the nickel content is too high, the battery life and thermal safety may decrease due to the reduced structural stability of the active material, and the manufacturing cost may increase.
[0062] In the positive electrode active material of Formula 1, cobalt may be present in an amount corresponding to y (0.05 ≤ y ≤ 0.2). If the cobalt content is too low, it may be difficult to simultaneously achieve sufficient rate capability and high powder density of the active material. If the cobalt content is too high, the overall cost of the raw materials will increase, and the reversible capacity may decrease.
[0063] In the positive electrode active material of Chemical Formula 1, manganese may be present in a content corresponding to z (i.e., 0 ≤ z ≤ 0.4 or 0.1 ≤ z ≤ 0.4). If the manganese content is too low, production costs may increase, and the stability of the positive electrode active material may decrease. If the manganese content is too high, the battery capacity and output characteristics may decrease.
[0064] In the positive electrode active material of Chemical Formula 1, the positive electrode active material may specifically contain Zr and Y, and the total content of Zr and Y, based on the weight of the positive electrode active material, is 3000 to 5800 ppm, more specifically, 4000 to 5200 ppm or 4200 to 5000 ppm. If it is below the range, the particle size growth may be negligible; if it is above the range, excess elements will be distributed at the precursor interface during calcination, which may hinder particle size growth. Therefore, when the total content of Zr and Y meets the range, single crystal particles in the positive electrode active material can be formed within an appropriate size range.
[0065] Furthermore, in a lithium secondary battery positive electrode active material according to an embodiment of the present invention, the surface portion of the positive electrode active material may include a coating layer. Specifically, the coating layer may include Al, W, Co, V, Ti, Nb, Ce, B, P, or a combination thereof.
[0066] More specifically, the coating layer comprises Al and W, and the W content ratio (W / Al) relative to the Al content can be greater than 0 and less than 4.0, more specifically, it can be greater than 0.5 and less than 3.0.
[0067] When the specified content ratio is met, it offers the advantage of improved discharge capacity and improved high-temperature lifespan. If the content ratio is exceeded, unstable LiWOx may form on the surface of the positive electrode active material or at the interface between single-particle positive electrode active materials, leading to a reduction in the improvement effect on high-temperature lifespan.
[0068] Preparation method of positive electrode active material for lithium secondary battery In another embodiment of the present invention, a method for preparing a positive electrode active material for a lithium secondary battery is provided, comprising the following steps: preparing a transition metal precursor containing 50 to 70 mol% nickel based on the total molar amount of the transition metal; mixing the transition metal precursor and lithium raw materials and then calcining to form a lithium transition metal oxide; and crushing the lithium transition metal oxide to form a monocrystalline lithium secondary battery positive electrode active material, wherein the crushing is carried out using compressed air at a crushing pressure of 3.4 to 4.5 bar, specifically 3.5 to 4.3 bar, and the calcination is carried out in an air atmosphere.
[0069] The following describes the preparation method of the positive electrode active material for lithium secondary batteries according to an embodiment of the present invention, step by step.
[0070] First, a transition metal precursor is prepared, which contains 50 to 70 mol% nickel based on the total moles of transition metals.
[0071] The nickel-containing transition metal precursor is not particularly limited; for example, it can be a transition metal hydroxide.
[0072] The transition metal hydroxide can be prepared, for example, by adding a complexing agent solution and a pH adjuster solution to a transition metal-containing solution containing nickel raw material and optionally cobalt or manganese raw material for a co-precipitation reaction.
[0073] There are no particular limitations on the nickel raw material, as long as it is a substance used in the preparation of precursors for positive electrode active materials in this art. For example, the nickel raw material can be a nickel-containing sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or hydroxyoxide, etc. Specifically, it can be NiSO4, NiSO4·6H2O, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, nickel salts of fatty acids, nickel halides, or combinations thereof, but is not limited thereto.
[0074] There are no particular limitations on the cobalt raw material, as long as it is a substance used in the preparation of precursors for positive electrode active materials in this art. For example, the cobalt raw material can be a cobalt-containing sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, or hydroxyoxide, etc. Specifically, it can be CoSO4, CoSO4·7H2O, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, or a combination thereof, but it is not limited to these.
[0075] There are no particular limitations on the manganese raw material, as long as it is a substance used in the preparation of precursors for positive electrode active materials in this art. For example, the manganese raw material can be a manganese-containing sulfate, acetate, nitrate, halide, sulfide, hydroxide, oxide, hydroxy oxide, or a combination thereof. Specifically, it can be manganese salts such as MnSO4, MnCO3, Mn(NO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese salts of fatty acids, manganese oxides such as Mn2O3, MnO2, and Mn3O4, hydroxy oxides, manganese chloride, or a combination thereof, but it is not limited to these.
[0076] The transition metal-containing solution can be prepared by adding nickel raw material and optionally cobalt or manganese raw material to a solvent, wherein the solvent is specifically water or a mixture of water and an organic solvent (e.g., alcohol) that can be uniformly mixed with water.
[0077] The complexing agent-containing solution serves to form a complex. The complexing agent may include, for example, NH3, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or combinations thereof, but is not limited thereto. Furthermore, the complexing agent-containing solution can be used in the form of an aqueous solution, in which case water or a mixture of water and an organic solvent (e.g., an alcohol) that is homogeneous with water can be used as the solvent.
[0078] At this point, by adjusting the concentrations of nickel, cobalt, and manganese raw materials, the molar ratio of nickel, cobalt, and manganese in the precursor can be adjusted.
[0079] Therefore, the nickel content in the transition metal precursor can be 50 to 70 mol, based on the total number of moles of transition metal.
[0080] In addition, the cobalt content in the transition metal precursor can be 5 to 20 mol, based on the total number of moles of transition metal.
[0081] Furthermore, based on the total number of moles of transition metals, the manganese content in the transition metal precursor can be 10 mol% or more, more specifically 15 mol%, 20 mol%, 25 mol%, 30 mol%, or 40 mol% or more.
[0082] The technical significance of adjusting the nickel, cobalt, and manganese content in transition metal precursors is the same as that mentioned above, so it is omitted.
[0083] Furthermore, in the step of mixing the transition metal precursor and lithium raw material to prepare the first mixture, a doping raw material may be further included. Specifically, the doping raw material may be a Zr raw material and a Y raw material.
[0084] The Zr raw material can be Zr(SO4)2, ZrS2, ZrO2, Zr(NO3)4 or a combination thereof, but is not limited to these.
[0085] The Y raw material can be Y(SO4)2, Y2(SO4)3, Y2O3, Y(NO3)3 or a combination thereof, but is not limited to these.
[0086] Next, the transition metal precursor and lithium raw material are mixed and calcined to obtain lithium transition metal oxide. Specifically, lithium transition metal oxide can be obtained through one to two calcinations.
[0087] Traditionally, lithium metal oxides are calcined at high temperatures for extended periods to form single-crystal forms. However, this process can lead to a decline in the electrochemical properties of the active material due to over-calcination causing nickel cation mixing and the formation of rock salt impurities. In contrast, the preparation method of this invention prevents these problems by adjusting the calcination temperature and time during a single or double calcination, and also improves particle strength, resulting in increased yield.
[0088] At this time, the atmosphere during calcination is not particularly limited. For example, it can be carried out in an air or oxygen (O2) atmosphere, but more specifically, it can be carried out in an air atmosphere. For cathode active materials with high nickel content, it is difficult to form a layered crystal structure when calcined in an air atmosphere, resulting in a significant decrease in electrochemical properties; therefore, it is usually carried out in an oxygen atmosphere. On the other hand, as described in this invention, when the nickel content is relatively low, even if calcination is carried out in an air atmosphere, the decrease in electrochemical properties is not significant, and process costs can be saved.
[0089] The calcination can be carried out at temperatures of 830 to 990°C, 840 to 980°C, 845 to 960°C, or 880 to 960°C, for a total duration of 8 to 20 hours, 9 to 18 hours, or 10 to 15 hours. The specific ranges for adjusting the calcination temperature and time are described in more detail below.
[0090] When the calcination consists of only one calcination, the calcination can be carried out at a temperature of 920 to 960°C or 930 to 950°C, and the calcination can last for a total of 8 to 16 hours or 10 to 14 hours. If the calcination temperature is below 930°C, specifically below 920°C, the growth of individual particles within the lithium transition metal oxide will decrease, and it may not be easy to form a single-crystal lithium transition metal oxide. If the calcination temperature is too high, overburning will occur, especially increasing the rock-salt structure crystalline phase on the surface of the positive electrode active material, which may lead to the deterioration of the electrochemical properties of the active material, such as capacity.
[0091] When the calcination includes primary and secondary calcination, the primary calcination can be carried out at temperatures of 920 to 960°C, 930 to 950°C, or 940 to 945°C; the secondary calcination can be carried out at temperatures of 840 to 920°C, 850 to 910°C, or 880 to 910°C; the primary and secondary calcination can be carried out for a total of 12 to 16 hours or 12 to 14 hours; the duration of the primary calcination can be equal to or greater than the duration of the secondary calcination. If the primary calcination temperature is below 930°C, specifically below 920°C, the growth of individual particles within the lithium transition metal oxide will decrease, and it may not be easy to form a single-crystal lithium transition metal oxide. If the primary calcination temperature is too high, over-burning will occur, especially increasing the rock-salt structure crystalline phase on the surface of the positive electrode active material, which may lead to deterioration of the electrochemical properties of the active material, such as capacity. More specifically, the secondary calcination time can be set to more than 6 hours. In this way, when the secondary calcination is carried out at a temperature lower than that of the primary calcination, the structural stability of the active material after the primary calcination can be improved, and the amount of heat required for the calcination of the active material can be reduced compared to the case where the primary calcination is carried out at a temperature above 930°C (specifically above 940°C), thereby saving process costs.
[0092] In particular, the secondary calcination, when carried out within the specified temperature and time range, can stabilize the crystal structure of the positive electrode active material, and is therefore preferred. Furthermore, the lithium byproducts remaining on the surface of the metal oxide decompose upon heating and diffuse into the interior of the metal oxide, thereby reducing the amount of lithium remaining on the surface. The lithium ions react with the surface of the metal oxide to form a stable layered structure, stabilizing the surface structure of the metal oxide. This has the advantage of improving the battery's resistance and lifespan characteristics, and is therefore preferred.
[0093] The first calcination and the second calcination do not include a cooling or pulverizing step. The first calcination and the second calcination are carried out continuously at different temperatures. This can suppress the reaction between external moisture and the calcined material, suppress the increase of residual lithium, suppress the deterioration of the active material caused by over-calcination, and stabilize the structure of the active material.
[0094] The method for preparing the positive electrode active material of the lithium secondary battery according to the present invention comprises the following steps: breaking down lithium transition metal oxide to obtain a positive electrode active material in the form of single particles or 1 to 20 said single particles aggregated together.
[0095] The decomposition can be carried out after cooling the calcined lithium transition metal oxide to 50 to 200°C. Cooling to this temperature can suppress the reaction between external moisture and the calcined material, and can also suppress the increase of residual lithium.
[0096] The decomposition can be performed using conventional methods in the art, such as rotor mills, jet mills, ball mills, pin mills, bead mills, or roller mills, particularly jet mills, and more specifically, air jet mills utilizing compressed air, at a crushing pressure of 3.4 to 4.5 bar, specifically 3.5 to 4.3 bar. The decomposition can be performed at different crushing pressures depending on the calcination temperature or time and the cohesive force between individual particles. However, when decomposition is performed within this range, the generation of unnecessary particle breakage leading to fine powder can be suppressed. This allows for the suppression of side reactions with the electrolyte during operation when the electrode containing the positive electrode active material is used in a secondary battery, and enables the separation of fully grown individual particles, thereby obtaining the desired stability of the single-crystal positive electrode active material.
[0097] Furthermore, after obtaining the single-crystal positive electrode active material through the aforementioned crushing step, the process may further include the following step: mixing the single-crystal positive electrode active material and the coating raw material, followed by heat treatment, to obtain a positive electrode active material with a coating layer formed on its surface. In this case, the technical definition, significance, and characteristics of the coating layer are as described above. The heat treatment can be performed at 400 to 500°C, more specifically at 410 to 450°C, and can last for 5 to 8 hours.
[0098] positive electrode In another embodiment of the present invention, a positive electrode is provided, the positive electrode comprising: a current collector; and a positive electrode active material layer located on one side of the current collector, and comprising a positive electrode active material prepared according to a foregoing embodiment.
[0099] The characteristics of the positive electrode active material constituting the positive electrode active material layer are the same as those described above. Therefore, a detailed description of the positive electrode active material is omitted.
[0100] For the current collector, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with surface treatments such as carbon, nickel, titanium, or silver can be used, for example.
[0101] In addition, the positive electrode active material layer may include an adhesive and a conductive agent.
[0102] At this point, the adhesive serves to improve the adhesion between the positive electrode active material particles and the bonding force between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), PVDF-co-HFP, polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof. These can be used individually or in mixtures of two or more, but are not limited to these. The adhesive can comprise 1 to 30% by weight relative to the total weight of the positive electrode active material layer.
[0103] Furthermore, the conductive agent is used to impart conductivity to the electrode, and its use is not particularly restricted as long as it does not cause chemical changes in the constructed battery and has electronic conductivity. Specific examples include graphite such as natural or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fiber; metal powders or fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. These can be used alone or in mixtures of two or more, but are not limited to these. The conductive agent typically comprises 1 to 30% by weight relative to the total weight of the positive electrode active material layer.
[0104] The positive electrode can be prepared according to conventional positive electrode preparation methods, except that it is prepared to meet the specified range.
[0105] Specifically, the positive electrode can be prepared by coating a positive electrode active material layer forming composition, optionally including a binder, conductive agent, or solvent as needed, onto a positive electrode current collector, followed by drying and pressing. In this case, the types and amounts of the positive electrode active material, binder, and conductive agent are as described above.
[0106] The solvent can be a commonly used solvent in this field, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water. One or a mixture of two or more of these can be used. The amount of solvent used, considering the coating thickness and yield of the slurry, should be sufficient to dissolve or disperse the positive electrode active material, conductive agent, and binder, and to achieve a viscosity that exhibits excellent thickness uniformity during subsequent coating preparation of the positive electrode.
[0107] Alternatively, the positive electrode can also be prepared by casting a positive electrode active material layer forming composition onto a separate support, peeling it off from the support to obtain a thin film, and then laminating the thin film onto the positive electrode current collector.
[0108] Lithium secondary batteries In yet another embodiment, a lithium secondary battery comprising the positive electrode is provided.
[0109] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, a separator between the positive and negative electrodes, and an electrolyte, wherein the positive electrode is as described above. Furthermore, the lithium secondary battery may optionally include a battery container housing an electrode assembly comprising the positive electrode, negative electrode, and separator, and a sealing member for sealing the battery container.
[0110] In the lithium secondary battery, the negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0111] For the negative electrode current collector, there are no particular restrictions as long as it does not cause chemical changes in the battery while maintaining high conductivity. For example, it can be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or copper or stainless steel, or aluminum-cadmium alloys, after surface treatment with carbon, nickel, titanium, silver, etc. Furthermore, the negative electrode current collector can typically have a thickness of 3 to 500 μm. Similar to the positive electrode current collector, fine irregularities can be formed on the surface of the current collector to enhance the adhesion of the negative electrode active material. For example, it can be in various forms such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0112] The negative electrode active material layer may optionally include a binder and a conductive agent together with the negative electrode active material. As an example, the negative electrode active material layer may also be prepared by coating a negative electrode active material layer forming composition comprising the negative electrode active material and optionally a binder and a conductive agent onto a negative electrode current collector and drying it, or by casting the negative electrode forming composition onto a separate support, peeling it off from the support to obtain a film, and then laminating the film onto the negative electrode current collector.
[0113] As the negative electrode active material, compounds capable of reversibly inserting and deintercalating lithium can be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metallic compounds that can be alloyed with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; lithium-doped and dedoped metal oxides such as SiOβ (0≤β≤2), SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the aforementioned metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites. Any one or a mixture of two or more of these can be used. Furthermore, a thin film of metallic lithium can also be used as the negative electrode active material. Additionally, both low-crystallinity carbon and high-crystallinity carbon can be used as carbon materials. As low-crystallinity carbon, soft carbon and hard carbon are representative examples. As highly crystalline carbon, amorphous, plate-like, flake-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, carbon microspheres, mesophase pitches, and petroleum and coal-based coke (coke derived from petroleum or coal tar pitch) are representative examples of high-temperature calcined carbon.
[0114] The adhesive and conductive agent may be the same as those previously described in the positive electrode.
[0115] Next, depending on the type of lithium secondary battery, a separator may also be present between the positive and negative electrodes. Such a separator can be made of polyethylene, polypropylene, polyvinylidene fluoride, or multilayer membranes of two or more layers thereof, or mixed multilayer membranes such as polyethylene / polypropylene two-layer membranes, polyethylene / polypropylene / polyethylene three-layer membranes, or polypropylene / polyethylene / polypropylene three-layer membranes.
[0116] Furthermore, in the lithium secondary battery, the electrolyte can be listed as organic liquid electrolyte, inorganic liquid electrolyte, solid polymer electrolyte, gel polymer electrolyte, solid inorganic electrolyte, molten inorganic electrolyte, etc., but is not limited to these.
[0117] Specifically, the organic liquid electrolyte may contain an organic solvent and a lithium salt.
[0118] As for the organic solvent, any solvent that can act as a medium for the migration of ions participating in the electrochemical reaction of the battery is not particularly limited in its use. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), and propylene carbonate can be used. Carbonate solvents such as carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group from C2 to C20, and may contain double bonds, aromatic rings, or ether bonds); amides such as dimethylformamide; dioxolane solvents such as 1,3-dioxolane; or sulfolane solvents. Among these, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant, and low-viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate), which can improve the charge-discharge performance of the battery, is preferred. In this case, using a mixture of cyclic carbonates and linear carbonates at a volume ratio of about 1:1 to about 1:9 can result in an electrolyte exhibiting excellent performance.
[0119] For the lithium salt, any compound capable of providing lithium ions for use in lithium secondary batteries can be used without particular restriction. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, etc., can be used. The concentration of the lithium salt is preferably in the range of 0.1 to 2.0 M. If the concentration of the lithium salt falls within this range, the electrolyte has appropriate conductivity and viscosity, thus exhibiting excellent electrolyte performance, and lithium ions can migrate effectively.
[0120] As described above, the lithium secondary battery containing the positive electrode according to the present invention stably exhibits excellent discharge capacity, output characteristics and capacity retention, and is therefore very useful in portable devices such as mobile phones, laptops, and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).
[0121] Preferred embodiments and comparative examples of the present invention are described below. However, the following embodiments are merely preferred embodiments of the present invention, and the scope of the present invention is not limited to the following embodiments.
[0122] Preparation of positive electrode active materials Example 1 (Mixed) The components are Ni 0.6 Co 0.1 Mn 0.3 The precursor (OH)2 and Li2CO3 are added to a mixer, and the amount added is controlled so that the molar ratio of lithium to the transition metal of the precursor (Li / M) is 1.06. Doping materials ZrO2 and Y2O3 are added and the amount added is controlled so that the contents of Zr and Y are 3000ppm and 1500ppm, respectively. Then, mechanical mixing is performed to form a mixture.
[0123] (Calcination and Decomposition) Subsequently, the mixture was heat-treated to 945°C in air, and then calcined at a constant temperature of 945°C for 14 hours, followed by natural cooling to form lithium transition metal oxide. Afterward, the lithium transition metal oxide was decomposed using an air jet mill to obtain a single-crystal cathode active material. The composition of the obtained single-crystal cathode active material is Li... 1.06 Ni 0.6 Co 0.1 Mn 0.3 O2.
[0124] (Coating and Heat Treatment) When mixing the monocrystalline positive electrode active material with Al2O3 and WO3 as coating raw materials, the amount added is controlled so that Al and W account for 1700 ppm and 3200 ppm of the total weight of the mixture, respectively. The mixture is mixed in a mixer and heat-treated at 420°C for 6 hours to obtain a monocrystalline positive electrode active material with a coating layer containing Al and W formed on the surface.
[0125] Examples 2 to 7 and Comparative Examples 1 to 8 Except for adjusting the calcination and decomposition conditions as shown in Table 1 below, the positive electrode active material was prepared using the same method as in Example 1.
[0126] Table 1
[0127] Experimental Example 1: Particle Perimeter Analysis of Positive Electrode Active Materials Using SEM Images For the positive electrode active materials prepared according to the embodiments and comparative examples, images of the positive electrode active materials were obtained using a SEM (scanning electron microscope) at 5000x magnification and 5kV. The SEM images of Examples 1 to 4, Comparative Examples 3 and 4 are shown below. Figures 1 to 6 middle.
[0128] Figures 1 to 6 These are SEM (scanning electron microscope) images obtained by magnifying the positive electrode active materials prepared according to the examples and comparative examples 5000x. (Refer to...) Figures 1 to 6 It can be confirmed that the prepared single-crystal positive electrode active material contains an average of 1 to 50 single particles (specifically 1 to 20).
[0129] For the obtained SEM images, image analysis based on an AI program was used to measure the perimeter, area, and circumcircle of each particle shown in the SEM images. Here, the circumcircle refers to an ideal circle containing the two or more outermost points of a single particle. This means that the interior of the circumcircle contains the entire area of the single particle.
[0130] Figures 7 to 12 These are images from SEM images of the positive electrode active materials prepared according to the examples and comparative examples, analyzed using an AI (artificial intelligence) program. Figures 7 to 12 The perimeter, area, and circumcircle of each single particle can be derived from the prepared positive electrode active material.
[0131] Specifically, after detecting particles from the SEM image, the area and perimeter of each particle are calculated using a simple Python function. The unit at this point corresponds to pixels, so a scale bar is used to convert to SI (International System of Units) units such as micrometers (μm).
[0132] Subsequently, assuming the perimeter of the measured particle to be the perimeter of an ideal circular particle (2πR1), the first diameter of the particle (D1=2πR1) was derived. R1), and the area of the measured particle is assumed to be the area of an ideal spherical particle (πR2). 2 After that, the second diameter of the particle (D2=2) was derived. R2). Furthermore, the third diameter of the particle (D3=2) was derived from the measured circumcircle diameter of the particle. R3).
[0133] Then, by calculating Equation 1 (D1) which represents the relationship between the first and third diameters. D2 / D3) can confirm the differences between the embodiments and the comparative examples.
[0134] The relevant results are shown in Table 2 below.
[0135] Table 2
[0136] Referring to Table 2, it can be confirmed that in the embodiment, formula 1 (D1) The diameters (D2 / D3) meet the range of 1.45 to 1.70 μm, specifically 1.50 to 1.68 μm, while the comparative examples do not meet this range. Furthermore, it can be confirmed that the first diameter (D1) in the embodiments meets the range of 1.90 to 2.39 μm, specifically 1.92 to 2.30 μm or 1.94 to 2.23 μm, while the comparative examples do not meet this range.
[0137] Furthermore, it can be confirmed that the second diameter (D2) in the embodiment satisfies the range of 1.40 to 2.10 μm, specifically 1.45 to 2.00 μm or 1.50 to 1.80 μm, while the comparative example does not satisfy this range.
[0138] Furthermore, it can be confirmed that the third diameter (D3) in the embodiment satisfies the range of 1.90 to 2.50 μm, specifically the range of 1.93 to 2.45 μm or 1.96 to 2.41 μm, while the comparative example does not satisfy this range.
[0139] Experimental Example 2: Analysis of the proportion of micro powder during the pressing of positive electrode active materials For the positive electrode active materials according to the examples and comparative examples, the following experiments were conducted to analyze the proportion of microparticles generated due to particle breakage when a predetermined pressure was applied to the positive electrode active material particles. It should be noted that the operation of applying pressure to the positive electrode active material can correspond to the pressing process used in the preparation of the positive electrode.
[0140] Specifically, 3.00g of positive electrode active material powder was placed into a mold with a diameter of 1.3cm, and a pressure of 67.8kN / cm was applied using a pressure device. 2 After pressurization, the pressurized granular positive electrode active material was placed in a mortar and ground to break up the aggregated particles. Then, 1 mL of 10 wt% (NaPO3)6 was added as a dispersant to 500 mL of water, and the broken-up positive electrode active material was added to the mixture. The mixture was then ultrasonically treated for approximately 1 minute. Subsequently, particle size analysis was performed using a Malvern (MS3000) instrument, and the proportion of microparticles with a particle size less than 1.0 μm was determined.
[0141] The relevant results are shown in Table 3 below.
[0142] Table 3
[0143] It has been confirmed that for those satisfying the aforementioned equation 1 (D1) The positive electrode active material (D2 / D3) according to the embodiment, when subjected to 67.8 kN / cm 2 At the specified pressure, the proportion of microparticles with a particle size of less than 1 μm is less than 5.0%. More specifically, the proportion of microparticles is 0.5% to 4.5%, 1.0% to 4.0%, 2.0% to 4.0%, or 2.1% to 3.6%. Accordingly, the generation of microparticles due to particle breakage can be reduced, and it is expected that gas generation problems caused by microparticles can ultimately be avoided, thereby maximizing battery safety.
[0144] Furthermore, particle breakage during the pressing process reduces the density between particles within the electrode and increases the contact resistance between particles, potentially degrading electrode performance. In other words, it can be confirmed that the positive electrode active material according to this embodiment has the effect of suppressing particle breakage during the pressing process and enhancing electrode performance.
[0145] However, it has been confirmed that for positive electrode active materials, exceeding the aforementioned Formula 1 (D1) In Comparative Examples 1 to 4, where the upper limit of the appropriate range of D2 / D3 was used, the proportion of micronized powder was also reduced.
[0146] However, when it exceeds Equation 1 (D1) During the D2 / D3 phase, excessive single-crystal growth occurs in the positive electrode active material, leading to significant structural shrinkage and inhibiting lithium-ion diffusion and extraction within the material. This may result in a decrease in electrode capacity and rate performance. Specifically, for Comparative Examples 1 to 4, capacity evaluation using a coin cell, as described later, confirmed that the electrochemical characteristics were impaired.
[0147] Experimental Example 3: Evaluation of Electrochemical Characteristics Using a Coin Cell For the positive electrode active materials according to the examples and comparative examples, coin batteries were prepared as follows to evaluate their physical properties and electrochemical performance.
[0148] Specifically, the positive electrode active material, polyvinylidene fluoride binder (trade name: KF9700) and carbon black conductive agent were mixed in a weight ratio of 96.5:1.5:2, and the mixture was added to N-methyl-2-pyrrolidone solvent to make the solids content reach about 60% by weight, thereby preparing the positive electrode active material slurry.
[0149] The slurry was coated onto an aluminum foil (20 μm thick) serving as the positive electrode current collector using a doctor blade. After drying, the foil was pressed to prepare the positive electrode. The loading of the positive electrode was approximately 16 mg / cm³. 2 The compacted density is approximately 3.5 g / cm³. 3 .
[0150] A 2032-type coin cell was prepared using the aforementioned positive electrode, lithium metal negative electrode (200 μm thick, Welcos), electrolyte, and polyethylene separator, following conventional methods. The electrolyte was a mixed solution obtained by dissolving 1 M LiPF6 in a mixed solvent (mixing ratio EC:DMC:DEC = 1:2:1 vol%), wherein the mixed solvent contained 2% VC (ethylene carbonate), ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).
[0151] (1) Evaluation of initial capacity and initial efficiency After fabricating the coin cell battery, it was aged at 25°C for 12 hours, followed by charge-discharge tests at 25°C. To evaluate the discharge capacity, a baseline capacity of 200 mAh / g was used, and the battery was charged at a constant current of 0.1C to 4.4V, then switched to constant voltage charging until the termination current reached 0.05C. After charging, a 10-minute rest time was allowed, followed by discharge at a constant current of 0.1C to 2.5V, again using 200 mAh / g as the baseline capacity.
[0152] (2) High-temperature life evaluation (45℃, 50 cycles) After fabricating the lithium-ion rechargeable battery half-cell, it was charged at 45°C with a constant current of 0.5C to 4.4V, then switched to constant voltage charging until the termination current reached 0.05C. After charging, a 10-minute rest time was allowed, followed by discharge at a constant current of 1.0C to 2.5V. Fifty charge-discharge cycles were performed under these conditions, and the capacity retention rate of the 50th cycle relative to the first cycle was calculated.
[0153] The resulting discharge capacity and high-temperature capacity retention characteristics are shown in Table 4 below.
[0154] Table 4
[0155] It has been confirmed that the aforementioned equation 1 (D1) is satisfied. The positive electrode active material according to the embodiment (D2 / D3) has a discharge capacity of 195.0 mAh / g or higher. More specifically, the discharge capacity is 195.0 to 200.0 mAh / g or 195.8 to 198.0 mAh / g.
[0156] Furthermore, it has been confirmed that the aforementioned equation 1 (D1) is satisfied. The positive electrode active material according to the embodiments, within a suitable range of D2 / D3, exhibits a high-temperature capacity retention of 96.0% or higher. More specifically, the high-temperature capacity retention is 95.3% to 96.4% or 96.1% to 96.4%. A high high-temperature capacity retention means that even when charged and discharged at high temperatures, the capacity does not decrease significantly, thus indicating excellent high-temperature lifetime characteristics.
[0157] For Comparative Examples 1 to 4, as mentioned above, although particle breakage was prevented, it was confirmed that the electrochemical characteristics were impaired. Specifically, it was confirmed that the discharge capacity was 196.0 mAh / g or less. Furthermore, the high-temperature capacity retention rate was 96.3% or more, specifically 96.3% to 96.5%, thus confirming that the lifetime characteristics at high temperatures were impaired.
[0158] In addition, for Comparative Examples 5 and 6, the discharge capacity was above 196.0 mAh / g and the high-temperature lifetime characteristic was below 95.2%. However, as mentioned above, the particles were severely broken during pressing, resulting in significant damage to stability.
[0159] Therefore, by comparing the examples with the comparative examples, it can be confirmed that the positive electrode active materials according to Examples 1 to 7 and the batteries containing them are excellent in electrochemistry and also have excellent stability.
[0160] Based on the results of comprehensive experimental examples, a positive electrode active material that can reduce the generation of micronized powder due to particle breakage, while possessing excellent electrochemical properties such as discharge capacity and high-temperature resistance increase rate, satisfies Equation 1 (D1 The appropriate range of D2 / D3) of the positive electrode active material according to Examples 1 to 7.
[0161] Furthermore, for lithium secondary batteries containing this positive electrode active material, it is anticipated that a lithium secondary battery can be provided that can prevent gas generation caused by microparticles, maximize battery safety, and achieve high capacity and long-term use at high temperatures.
[0162] This invention is not limited to the embodiments described above, and can be prepared in various different ways. Those skilled in the art will understand that other specific methods can be used without changing the technical concept or essential features of the invention. Therefore, it must be understood that the embodiments described above are exemplary in all respects and not restrictive.
Claims
1. A positive electrode active material for lithium secondary batteries, wherein, The positive electrode active material of the lithium secondary battery is a monocrystalline lithium secondary battery positive electrode active material. The positive electrode active material comprises 1 to 20 individual particles aggregated together, wherein each individual particle satisfies the following formula 1: [Formula 1] 1.40μm≤(D1 D2) / D3≤1.70μm In Equation 1, D1 refers to the first diameter of a single particle derived from the perimeter of a single particle measured in the SEM (scanning electron microscope) image of the positive electrode active material, assuming it to be the perimeter of an ideal circle (2πR1). (D1=2πR1) R1), D2 refers to the area of a single particle measured in the SEM image of the positive electrode active material, assumed to be the area of an ideal circle (πR2). 2 The second diameter of a single particle (D2=2) was derived afterward. R2), D3 refers to the third diameter of a single particle derived from the circumcircle diameter of the particle measured in the SEM image of the positive electrode active material (D3=2). R3).
2. The lithium secondary battery positive electrode active material according to claim 1, wherein, The D1 ranges from 1.90 to 2.39 μm.
3. The lithium secondary battery positive electrode active material according to claim 1, wherein, The D2 ranges from 1.40 to 2.10 μm.
4. The lithium secondary battery positive electrode active material according to claim 1, wherein, The D3 ranges from 1.90 to 2.50 μm.
5. The lithium secondary battery positive electrode active material according to claim 1, wherein, The positive electrode active material is subjected to a force of 67.8 kN / cm. 2 After pressurization, in the volume-based particle size distribution curve of the positive electrode active material, the proportion of micro-powder with a size of less than 1.0 μm is less than 5.0%.
6. The lithium secondary battery positive electrode active material according to claim 1, wherein, For the positive electrode active material, when the volume-based particle size distribution of the positive electrode active material is measured, the average particle size (D50) is 2.0 to 5.5 μm.
7. The lithium secondary battery positive electrode active material according to claim 1, wherein, The positive electrode active material is represented by the following chemical formula 1: [Chemical Formula 1] Li a [Ni x Co y Mr z M w ]O2 In the chemical formula 1, 0.8≤a≤1.2, 0.5≤x≤0.7, 0.05≤y≤0.2, 0≤z≤0.4, 0≤w≤0.2, x+y+z+w=1, and M is Zr, Y, B, Al, Mg, Ti, Nb, W, Sc, Si, V, Fe, Y, Mo, Ce, Hf, Ta, La, Sr or a combination thereof.
8. The lithium secondary battery positive electrode active material according to claim 7, wherein, The positive electrode active material contains Zr and Y. The total content of Zr and Y, based on the weight of the positive electrode active material, is 3000 to 5800 ppm.
9. The lithium secondary battery positive electrode active material according to claim 1, wherein, The positive electrode active material includes a coating layer on its surface, and the coating layer contains Al, W, Co, V, Ti, Nb, Ce, B, P or a combination thereof.
10. The lithium secondary battery positive electrode active material according to claim 9, wherein, The coating layer comprises Al and W. The ratio of W content to Al content (W / Al) is greater than 0 and less than 4.
0.
11. A method for preparing a positive electrode active material for a lithium secondary battery, comprising the following steps: Prepare a transition metal precursor containing 50 to 70 mol% nickel based on the total molar amount of transition metals; The transition metal precursor and lithium raw material are mixed and calcined to form lithium transition metal oxide; and The lithium transition metal oxide is broken down to form a monocrystalline lithium secondary battery positive electrode active material. The disintegration is carried out at a crushing pressure of 3.4 to 4.5 bar. The calcination is carried out in an air atmosphere.
12. The method for preparing the positive electrode active material of a lithium secondary battery according to claim 11, wherein, The calcination is carried out at a temperature of 830 to 990°C. The calcination process takes a total of 8 to 20 hours.
13. The method for preparing the positive electrode active material of a lithium secondary battery according to claim 11, wherein, The calcination consists of only one calcination. The first calcination is carried out at a temperature of 920 to 960°C. The calcination process takes a total of 8 to 16 hours.
14. The method for preparing the positive electrode active material of a lithium secondary battery according to claim 11, wherein, The calcination includes primary calcination and secondary calcination. The first calcination is carried out at a temperature of 920 to 960°C. The secondary calcination is carried out at a temperature of 840 to 920°C. The primary and secondary calcination processes take a total of 12 to 16 hours. The time for the first calcination is equal to or greater than the time for the second calcination.
15. A lithium secondary battery, wherein, The lithium secondary battery includes a lithium secondary battery positive electrode, and the lithium secondary battery positive electrode includes the positive electrode active material according to any one of claims 1 to 10.
Citation Information
Patent Citations
Display apparatus
KR1020240043323A